Implantación de un sistema de costos por procesos a la asociación de productores de queso y leche “La Unión”, ubicada en la parroquia Belisario Quevedo de la provincia de Cotopaxi, para el período 2010 - De la Cruz, Bertha (2010)
The investigation is focused in the Installation of a Cost System by Processes to the Association of Producers of Cheese and Milk “The Union”, by means of this system can know the real cost of the fresh cheese, for that it was considered three elements of cost and they are: Raw material, Manpower and Indirecting Cost, I facilitated the power to establish an accessible and just price and for the sale of the consumer. For the realization of the work it was used the descriptive, bibliographical investigation, the non experimental methodology using theoretical and analytic methods and with documents of the company and among the utilized techniques, the applied interview to the whole personnel of the Association allowing to know their organization, production; as well as the form of taking their daily registrations and the direct observation to the process of production of fresh cheese to achieve bigger grade of objectivity in the knowledge of the reality and to obtain all the necessary date.